Shakespeare's learning futures: The application of Shakespeare's allegory as interpretative scheme for sustainable decision-making. (March 2019) - Casteren van Cattenburch, Iris Hanna; Duijn, Michael
Highlights: Shakespeare's allegories can be applied to prompt multi-perspective reflection on the development of complex processes. The allegorist's pattern deepens the work of the learning historian because allegory invites to interpreting (rather than simply following or responding to) a narrative. Shakespeare can be applied to topical sustainability challenges, because allegory is directed towards the discovery of value. Shakespeare's allegorical pattern enriches the narrative strategy for learning and anticipating sustainable futures. Allegorical reflection of a sustainability challenge anticipates alternative futures, for more integral decision making. Abstract: William Shakespeare's works can be employed to articulate values worthy of pursuit and reflect learning histories, thus facilitating organizational learning for sustainable futures. The authors argue that Shakespeare's allegories allude to recognizable representations of everyday life, and are built on a 'plan' that can be employed to perceive a patterned mirroring between the allegory and the learning history of a sustainability challenge. This mirroring exercise procreates the articulation of organizational challenges, an understanding of roles and motives of actors involved, the notion of plural perspectives and their dynamic correlation over time, and the anticipation of sustainability narratives for organizational learning. The 'plan' on which Shakespeare's plays are based is an immanent cyclical pattern of affirmative and adversative value orientations, whose disintegration engenders unsustainable tendencies, which finds support in recent sustainability theory. Analysis of the nature and effect of these combined value orientations becomes an instrument to recognize values worthy of pursuit and implement these in the learning process. This article demonstrates how to identify such value patterns in The Tempest and how to build on these patterns in a recent learning history of the renovation process of a monumental bridge in the City of Amsterdam.